Measurement Invariance of Personal Well-Being Index (Pwi-8) Across 26 Countries - Wlodarczyk, A (Springer Netherlands, 2017)
This report examines the measurement invariance of the Personal Well-being Index with 8 items (PWI-8). University students (N = 5731) from 26 countries completed the measure either through paper and pencil or electronic mode. We examined uni-dimensional structure of PWI and performed a Multi-group CFA to assess the measurement invariance across the 26 countries, using conventional approach and the alignment procedure. The findings provide evidence of configural and partial metric invariance, as well as partial scalar invariance across samples. The findings suggest that PWI-8 can be used to examine correlates of life satisfaction across all included countries, however it is impossible to compare raw scores across countries. © 2016, Springer Science+Business Media Dordrecht.